2007
DOI: 10.1163/156853707x208512
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Class and Cognition: Evidence from Italy

Abstract: East Asians have been found to reason in relatively holistic fashion and Americans in relatively analytic fashion. It has been proposed that these cognitive diff erences are the result of social practices that encourage interdependence for Asians and independence for Americans. If so, cognitive diff erences might be found even across regions that are geographically close. We compared performance on a categorization task of relatively interdependent southern Italians and relatively independent northern Italians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 18 publications
0
44
0
4
Order By: Relevance
“…Cultural background A body of literature has shown that cognitive styles differ substantially across cultures [43][44][45][46][47]. A well-known example of such a difference is analytic versus holistic.…”
Section: Cannabis Usementioning
confidence: 99%
“…Cultural background A body of literature has shown that cognitive styles differ substantially across cultures [43][44][45][46][47]. A well-known example of such a difference is analytic versus holistic.…”
Section: Cannabis Usementioning
confidence: 99%
“…En términos generales, estos refieren a característi-cas más bien vagas que a resultados determinantes. Knight y Nisbett (2007), por ejemplo, han encontrado que los asiáticos estarían inclinados a razonar y percibir de una manera más holística, a hacer hincapié en relaciones y similitudes entre objetos y eventos, y a deslizarse en un amplio campo perceptual. Los occidentales, en cambio, tenderían a razonar de forma más analítica, a focalizar en un objeto central y a razonar utilizando reglas y categorías.…”
Section: Culturaunclassified
“…En este sentido, se sabe que los asiáticos del este son más dependientes entre sí, y tienden a centrar su atención en el mundo social y el campo como un todo. Por su parte, los occidentales suelen ser menos dependientes, y tendientes a focalizar su atención en un objeto único (Knight y Nisbett, 2007).…”
Section: Culturaunclassified
“…12], and in cultural studies since the 1960s [13]. Biases have even been found in populations assumed to be relatively homogeneous, such as comparisons of Northern and Southern Italians [14] or Eastern and Western Europeans [15]. Adding studies involving cultures known to differ considerably exacerbates the difficulty of solving the response bias problem.…”
Section: Rating Scale Response Biasesmentioning
confidence: 99%